Effect of different oxide and hybrid precursors on MOF-CVD of ZIF-8 films. Issue 20 (10th May 2021) - Cruz, Alexander John; Arnauts, Giel; Obst, Martin; Kravchenko, Dmitry E.; Vereecken, Philippe M.; De Feyter, Steven; Stassen, Ivo; Hauffman, Tom; Ameloot, Rob
Abstract : Vapor-phase fabrication of the metal–organic framework ZIF-8 through the conversion of precursors prepared by physical, atomic, and molecular layer deposition. Abstract : Chemical vapor deposition of metal–organic frameworks (MOF-CVD) will facilitate the integration of porous and crystalline coatings in electronic devices. In the two-step MOF-CVD process, a precursor layer is first deposited and subsequently converted to a MOF through exposure to linker vapor. We herein report the impact of different metal oxide and metalcone layers as precursors for zeolitic imidazolate framework ZIF-8 films.